2013
DOI: 10.1378/chest.12-1676
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Assessment of Acute Dyspnea in the ED

Abstract: Background:We compared the ability of noninvasive measurements of cardiac output (CO) and thoracic fluid content (TFC) and their change in response to orthostatic challenges to diagnose acute decompensate heart failure (ADHF) from non-ADHF causes of acute dyspnea in patients in the ED.Methods:Forty-five patients > 44 years old presenting in the ED with dyspnea were studied. CO and TFC were monitored with a NICOM bioreactance device. CO and TFC were measured continuously while each patient was sitting, supine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
1
5
0
1
Order By: Relevance
“…In agreement with previous data 1, 3,37,38 , the accuracy of the initial clinical work-up for ADHF diagnosis was only moderate. The LUS-implemented approach increased the sensitivity and specificity of clinical assessment by 11.7% and 7.4%, respectively, with a NRI of 19.1%, which shows a relevant diagnostic impact of LUS in this setting.…”
Section: Discussionsupporting
confidence: 91%
“…In agreement with previous data 1, 3,37,38 , the accuracy of the initial clinical work-up for ADHF diagnosis was only moderate. The LUS-implemented approach increased the sensitivity and specificity of clinical assessment by 11.7% and 7.4%, respectively, with a NRI of 19.1%, which shows a relevant diagnostic impact of LUS in this setting.…”
Section: Discussionsupporting
confidence: 91%
“…It was not the purpose of this study to validate this variable, which has recently demonstrated to diagnose acute decompensated heart failure in an emergency department. 24…”
Section: Discussionmentioning
confidence: 99%
“…StO 2 VOT-derived estimation of cardiovascular stress during a spontaneous breathing trials (increased DeO 2 ) also identified patients who subsequently failure that trial [37]. Furthermore, Guyette et al [38], measured both the VOT StO 2 as baseline serum lactate, known to define existing cardiovascular insufficiency in trauma, in a cohort of trauma patients during the air transport to the Trauma Center.…”
Section: Identification Of Cardiovascular Insufficiencymentioning
confidence: 99%